Kurs Idr, Kurs Jpy, Indeks Djia, Serta Harga Minyak Dunia terhadap IDX pada Tahun 2017-2021 - Nurwulandari, Andini (IPM2KPE, 2025)
This study aims to analyze the development of the index of the influence of the IDR exchange rate, JPY exchange rate, DJIA index, and world oil prices on IDX to find out how the development of stock price index to IDR, JPY exchange rate, DJIA index, and world oil prices to IDX in 2017-2021 . The research method used is descriptive quantitative. The analytical method used is a statistical method, namely multiple linear regression analysis. The results showed, based on the linear regression test, the equation was obtained, namely IDX t = -4040.77 -0.144IDR + 50.011JPY + 0.113DJIA + 0.237oil + 0.492 IDX t-1. In conclusion, the IDR exchange rate, JPY exchange rate, DJIA, and world oil prices together have a positive and significant effect on the dependent variable, namely IDX. Keywords: DJIA Index, World Oil Prices, Indonesia Stock Exchange (IDX)